THE EFFECTIVENESS OF THE READ ANSWER DISCUSS EXPLAIN CREATE LEARNING MODEL IN IMPROVING CRITICAL THINKING SKILLS IN SCIENCE IN GRADE IV OF ELEMENTARY MADRASAH - Erfayliana, Yudesta (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Critical thinking skills are very important in the world of education, because they can help students develop a deep understanding of a material and make the right decisions. Critical thinking is a skill that students need to identify problems well. Students' critical thinking skills are still low due to the use of conventional learning methods. As a solution, this study applies the RADEC model which involves active student interaction through various stages, such as reading, answering, discussing, explaining, and creating. The results of the analysis show that the application of this model increases students' posttest scores in the experimental class compared to the control class using traditional methods. The RADEC model not only improves understanding of the material, but also students' critical thinking skills. In conclusion, the RADEC model has proven effective in developing students' critical thinking skills, and is recommended to be applied more widely in various educational contexts to prepare students to face the challenges of the 21st century.